Comparison of antibodies hydrolyzing myelin basic protein from the cerebrospinal fluid and serum of patients with multiple sclerosis. - Visilii B Doronin (Public Library of Science (PLoS), 2014)
It was found that antibodies (Abs) against myelin basic protein (MBP) are the major components of the antibody response in multiple sclerosis (MS) patients. We have recently shown that IgGs from sera of MS patients are active in the hydrolysis of MBP. However, in literature there are no available data concerning possible MBP-hydrolyzing Abs in cerebrospinal fluid (CSF) of MS patients. We have shown that the average content of IgGs in their sera is about 195-fold higher than that in their CSF. Here we have compared, for the first time, the average content of lambda- and kappa-IgGs as well as IgGs of four different subclasses (IgG1-IgG4) in CSF and sera of MS patients. The average relative content of lambda-IgGs and kappa -IgGs in the case of CSFs (8.0 and 92.0%) and sera (12.3 and 87.7%) are comparable, while IgG1, IgG2, IgG3, and IgG4: CSF - 40.4, 49.0, 8.2, and 2.5% of total IgGs, respectively and the sera - 53.6, 36.0, 5.6, and 4.8%, decreased in different order. Electrophoretically and immunologically homogeneous IgGs were obtained by sequential affinity chromatography of the CSF proteins on protein G-Sepharose and FPLC gel filtration. We present first evidence showing that IgGs from CSF efficiently hydrolyze MBP and that their average specific catalytic activity is unpredictably ∼54-fold higher than that of Abs from sera of the same MS patients. Some possible reasons of these findings are discussed. We suggest that anti-MBP abzymes of CSF may promote important neuropathologic mechanisms in this chronic inflammatory disorder and in MS pathogenesis development.